Evaluasi Pertumbuhan dan Produksi Padi Gogo Haploid Ganda Toleran Naungan dalam Sistem Tumpang sari - Priatna Sasmita; Bambang S. Purwoko; S. Sujiprihati; I. Hanarida; I. S. Dewi; M. A. Chozin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
Three doubled haploid (DH) upland rice lines obtained from anther culture having good agronomic and shade  tolerant traits were planted in an intercropping with maize. Their  monoculture systems were also included.  Those lines were GI-8, IG-19, and IW-56. Jatiluhur was also treated similar as shade tolerant control cultivar. The experiment was arranged in randomized complete block design with three replications. The treatments consisted of eight intercropping systems, four monoculture systems of rice, and two monoculture systems of maize. The result showed that all of tested DH lines were consistently shade tolerant under intercropping condition. The characteristics was represented by  similar growth and grain yield with  Jatiluhur under  intercroping system. The highest grain yield was 2.49 t/ha resulted by GI-8 and IG-19 lines  at the time that Jatiluhur was 2.36 t/ha. The intercropping of DH lines with  maize also showed the Land Equivalent Ratio (LER) =1.33-1.58, while Jatiluhur LER = 1.25-1.28, indicating that agronomically they were more advantageous than those in the monoculture system.   Key words :  Doubled haploid,, intercropping system, shade tolerant lines